Specific interactions between functionalised particles and circulating tumour cells. Issue 1 (1st March 2014) - Stamm, Matthew T.; Trickey‐Glassman, Andrew S.; Jiang, Linan; Zohar, Yitshak
Abstract : Receptor–ligand binding has been one of the more popular approaches to specifically targeting tumour cells. In this work, targeting efficiency was quantitatively characterized using silica particles functionalized with EpCAM antibodies and EpCAM‐expressing BT‐20 breast cancer cells. The effects of incubation time and particle concentration on the number of functionalised particles bound to target cells were experimentally investigated. The number of bound particles was found to increase with particle concentration, but not necessarily with incubation time. Binding affinity loss because of cell–particle–cell interaction was identified as a limiting mechanism for the number of particles bound to target cells. While cell‐surface coverage because of bound particles rises exponentially under low particle concentration, it features a peak value at high particle concentration. The current findings suggest that separation of a bound particle from a cell may be detrimental to cellular binding affinity.